Nuclear factor erythroid‐derived 2–related factor 2 activates glutathione S‐transferase expression in the midgut of Spodoptera litura (Lepidoptera: Noctuidae) in response to phytochemicals and insecticides. Issue 4 (10th May 2018) - Chen, S.; Lu, M.; Zhang, N.; Zou, X.; Mo, M.; Zheng, S.
Abstract: Detoxication enzymes play an important role in insect resistance to xenobiotics such as insecticides and phytochemicals. We studied the pathway for activating the expression of glutathione S‐transferases (GSTs) in response to selected xenobiotics. An assay of the promoter activity of GST epsilon 1 ( Slgste1 ) of Spodoptera litura led to the discovery of a cis‐regulating element. An antioxidant response element was activated in response to indole‐3‐carbinol (I3C) and chlorpyrifos (CPF) and was able to bind with the xenobiotic sensor protein nuclear factor erythroid‐derived 2–related factor 2 (SlNrf2). SlNrf2 and Slgste1 were responsive to reactive oxygen species induced by I3C and CPF in a S. litura cell line, as well as in S. litura midguts. SlNrf2 RNA interference (RNAi) reduced the message RNA levels of Slgste1 and the peroxidase activity of GSTs in response to I3C, xanthotoxin, CPF and deltamethrin. SlNrf2 RNAi and inhibitor treatment of GST activity decreased the viability of I3C‐treated cells. These results indicate that SlNrf2 activates the expression of GSTs in response to oxidative stresses caused by exposure to xenobiotics.